IL-27 alters inflammatory cytokine expression and limits protective immunity against Mycobacterium tuberculosis in a neonatal BCG vaccination model - Bradford, Shelby D.; Ryan, Kenneth J.; Divens, Ashley M.; Povroznik, Jessica M.; Bonigala, Sunilkanth; Robinson, Cory M. (Frontiers in Immunology, 2024)
Background Efforts to control tuberculosis (TB), caused by the pathogen Mycobacterium tuberculosis (Mtb), have been hampered by the immense variability in protection from BCG vaccination. While BCG protects young children from some forms of TB disease, long-term protection against pulmonary disease is more limited, suggesting a poor memory response. New vaccines or vaccination strategies are required to have a realistic chance of eliminating TB disease. In TB endemic areas, routine immunization occurs during the neonatal period and as such, we hypothesized that inadequate protective immunity elicited by BCG vaccination could be the result of the unique early-life immune landscape. Interleukin (IL)-27 is a heterodimeric cytokine with immune suppressive activity that is elevated in the neonatal period. Objective We investigated the impact of IL-27 on regulation of immune responses during neonatal BCG vaccination and protection against Mtb. Methods Here, we used a novel model of neonatal vaccination and adult aerosol challenge that models the human timeline of vaccine delivery and disease transmission. Results Overall, we observed improved control of Mtb in mice unresponsive to IL-27 (IL-27Rα-/-) that was consistent with altered expression patterns of IFN-γ and IL-17 in the lungs. The balance of these cytokines with TNF-α expression may be key to effective bacterial clearance. Conclusions Our findings suggest the importance of evaluating new vaccines and approaches to combat TB in the neonatal population most likely to receive them as part of global vaccination campaigns. They further indicate that temporal strategies to antagonize IL-27 during early life vaccination may improve protection.